The Star trek book - Ruditis, Paul (DK Publishing, 2021)
Re-engage! The new edition of The Star Trek Book takes readers even further into one of the greatest science fiction universes ever created. This unique, insightful, and comprehensive examination of an enduring, much loved franchise features every era of Star Trek in one volume, from the pioneering 1960s TV series to the latest movies and streaming shows, including Star Trek: Beyond, Star Trek: Discovery, Star Trek: Picard, and Star Trek: Short Trek. Written by Star Trek experts, this book is packed with stunning film and TV stills, illuminating infographics, and incisive, specially curated essays that unlock the mysteries of the ever-expanding Star Trek Universe. From new and legendary heroes such as James T. Kirk, Jean-Luc Picard, and Michael Burnham to iconic villains like Khan, Q, and the Borg, to fascinating alien species like the Vulcans, Klingons, and Ferengi, this book explores the central characters, technology, civilizations, and events that have shaped the complex, epic story of Star Trek. Resistance is futile. This is the (star) trek of a lifetime you don't want to miss!